Exploring a Tiriti-based superdiversity paradigm within early childhood care and education in Aotearoa New Zealand. (March 2023) - Chan, Angel; Ritchie, Jenny
This article reports findings from a study that used a process of document analysis to examine early childhood care and education responses to increasing superdiversity in the 'bicultural' legislative context of Aotearoa New Zealand. The New Zealand Education Review Office has described both Indigenous Māori children and 'children of migrants and refugees' as 'vulnerable' and 'priority learners'. This article uses the lenses of Te Tiriti o Waitangi (Indigenous rights) and Steven Vertovec's superdiversity approach to examine the implications of representations of the Indigenous Māori and the settler population in early childhood care and education in Aotearoa New Zealand. It further applies Sara Ahmed's diversity work on a phenomenology of whiteness to scrutinise the New Zealand government's commitments to supporting its nation's 'priority learners'.